Dynamics of Civil Structures, Volume 2 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Pakzad, Shamim; Juan, Caicedo (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Dynamics of Civil Structures, Volume 2. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the second volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early fi ndings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Modal Parameter Identifi cation • DynamicTesting of Civil Structures • Human Induced Vibrations of Civil Structures • Model Updating • Operational Modal Analysis • Damage Detection • Bridge Dynamics • Experimental Techniques for Civil Structures • Hybrid testing • Vibration Control of Civil Structures.